Analysis of the Influence of Credit Risk, Liquidity Risk, and Operational Risk on Banking Financial Performance in Financial Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 Period - Liana, Jenny; Kusumastuti, Ratih; Hizazi, Achmad (Journal of Comprehensive Science, 2025)
This study aims to analyze the influence of credit risk, liquidity risk, and operational risk on banking financial performance, especially profitability as measured using Return on Assets (ROA). The research population includes all conventional banks listed on the Indonesia Stock Exchange during the 2022–2024 period. The sample was determined using a purposive sampling technique, yielding 43 banks that met the research criteria. Data were collected from the banks' annual reports and official financial statements, which contain information related to NPL (Non-Performing Loan), LDR (Loan to Deposit Ratio), and BOPO (Operating Costs to Operating Income). The analysis was carried out using panel data regression, classical assumption tests (normality and multicollinearity), and hypothesis tests such as t-tests and determination tests (Adjusted R²). The results showed that partially, credit risk (NPL) had no significant effect on profitability, suggesting that the credit quality of the sample banks was relatively maintained or that the NPL factor was not yet a major pressure on performance. On the other hand, liquidity risk (LDR) had a significant positive effect on ROA, indicating that optimal liquidity management supports increased profitability. Operational risk (BOPO) had a significant negative effect on ROA, confirming that operational efficiency is a key factor in maintaining the bank's financial performance. These findings provide practical implications for bank management in optimizing liquidity and reducing operational costs to increase profitability in a sustainable manner.